The type IIB supernova 2011DH from a supergiant progenitor - Bersten, Melina (2012)
A set of hydrodynamical models based on stellar evolutionary progenitors is used to study the nature of SN 2011dh. Our modeling suggests that a large progenitor star —with R 200 R⊙—, is needed to reproduce the early light curve of SN 2011dh. This is consistent with the suggestion that the yellow super-giant star detected at the location of the SN in deep pre-explosion images is the progenitor star. From the main peak of the bolometric light curve and expansion velocities we constrain the mass of the ejecta to be 2 M⊙, the explosion energy to be E = 6 − 10 × 1050 erg, and the 56Ni mass to be approximately 0.06 M⊙. The progenitor star was composed of a helium core of 3 to 4 M⊙ and a thin hydrogen-rich envelope of 0.1 M⊙ with a main sequence mass estimated to be in the range of 12–15 M⊙. Our models rule out progenitors with helium-core masses larger than 8 M⊙, which correspond to MZAMS & 25 M⊙. This suggests that a single star evolutionary scenario for SN 2011dh is unlikely.